2016
DOI: 10.1002/jbm.a.35906
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of innate immune response in mouse primary cultured sertoli cells caused by nanoparticulate TiO2 involves the TAM/TLR3 signal pathway

Abstract: Sertoli cells provide appropriate mitogens, differentiation factors and sources of energy for developing germ cells throughout the lifetime of males, and protect these germ cells from harmful agents and from the host's own immune system. Therefore, reductions in the rate and quality of spermatogenesis caused by nanoparticulate titanium dioxide (nano-TiO ) may be closely involved in the immunoregulation of Sertoli cells. However, the underlying mechanism of this response is still unclear. To address this issue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…Our experiments clearly demonstrated that nano-TiO 2 reduced the activity of primary cultured rat LCs (Figure 6), entered the cytoplasm and nuclei of cells (Figures 7 and 8), and caused mitochondrial membrane injury (Figure 9), consistent with results obtained with primary cultured mouse or rat Sertoli cells. 42,43 Simultaneously, testosterone production in LCs was significantly lowered following nano-TiO 2 treatment ( Figure 10). Mitochondrial damage is associated with dysfunction of LCs, which are involved mainly in the production and secretion of testosterone.…”
Section: Discussionmentioning
confidence: 95%
“…Our experiments clearly demonstrated that nano-TiO 2 reduced the activity of primary cultured rat LCs (Figure 6), entered the cytoplasm and nuclei of cells (Figures 7 and 8), and caused mitochondrial membrane injury (Figure 9), consistent with results obtained with primary cultured mouse or rat Sertoli cells. 42,43 Simultaneously, testosterone production in LCs was significantly lowered following nano-TiO 2 treatment ( Figure 10). Mitochondrial damage is associated with dysfunction of LCs, which are involved mainly in the production and secretion of testosterone.…”
Section: Discussionmentioning
confidence: 95%
“…The very few studies describing the detrimental effect of TiO 2 NPs on SCs have been performed in mice and rat models under acute exposures (26)(27)(28). However, these experimental conditions may greatly differ from those under which human exposure can potentially occur and often result in conflicting data that are not applicable for risk assessment studies (29).…”
Section: Introductionmentioning
confidence: 99%